2005
DOI: 10.5713/ajas.2005.966
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Indigenous Browses and Sunflower Seed Cake Supplementation on Intake and Growth Performance of Dual-purpose Goats Fed Buffel Grass (Cenchrus ciliaris) Hay

Abstract: A study to compare the effects of supplementing Delonix elata, Grewia similis, Tamarindus indica and sunflower seed cake on intake and growth rate of dual-purpose goats fed low quality Buffel grass (Cenchrus ciliaris) hay was carried out. Twenty-eight male goats aged five to seven months (mean weight 12.93±3.94 kg) were randomly allocated to four dietary groups in a completely randomised design. The diets were hay plus Grewia similis, hay plus Delonix elata, hay plus Tamarindus indica and hay plus sunflower se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…Nutritional value of all three dietary treatments in terms of ME (Table 1) was sufficient to meet the requirement of growing indigenous goats. The ADG in goats in the present study was within the range reported by Goromela et al (1997) and Komwihangilo et al (2005) for Blended goats fed grass hay combined with leaf meal or concentrates. The lack of significant ADG differences between BG or CG and the concentrate-based diet shows that B. brizantha cv.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nutritional value of all three dietary treatments in terms of ME (Table 1) was sufficient to meet the requirement of growing indigenous goats. The ADG in goats in the present study was within the range reported by Goromela et al (1997) and Komwihangilo et al (2005) for Blended goats fed grass hay combined with leaf meal or concentrates. The lack of significant ADG differences between BG or CG and the concentrate-based diet shows that B. brizantha cv.…”
Section: Discussionsupporting
confidence: 88%
“…During the dry season, goats in highinput (intensive) production systems may be fed concentrates, e.g. agriculture mill by-products as supplementary diet (Komwihangilo et al, 2005;. These concentrates are expensive due to high demand from farmers rearing different livestock species, and large volumes are needed in extensive systems to feed large goat herds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low CP values, coupled with low digestibility of pastures mean that insufficient bulk would be available to satisfy the animal CP requirement for maintenance and production (Leng, 1990). Ruminant production in the tropics is limited by inadequate nitrogen from low quality forages such as hays, straws and stovers, which often contain as low as 20–50 g kg −1 CP in the DM and so do not meet the minimum CP requirement of 80 g kg −1 DM for optimal rumen microbial function (Komwihangilo et al. , 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, indigenous trees and shrubs leaf meals were used to replace conventional supplements like SFC and were shown to have high growth rates in goats (21g/day) compared to 7g/day for goats fed SFC. 32 Indigenous plants have also been shown to possess medicinal effects in the animals.…”
Section: Improvement In Animal Nutritionmentioning
confidence: 99%